Inheritance of Rose-Flowered Mutation in Chickpea Cicer arietinum L. - Hüseyin Çancı; Nisa Ertoy İnci; Fatma Öncü Ceylanbaloğlu (Journal of Agricultural Sciences)
Mutations are the most important phenomenon in the living organisms including plant species due to creating variation. Variation in crop plants can be increased by induced mutations. The present study deals with inheritance of an induced mutation with rose-flowered in the cultivated chickpea Cicer arietinum L. . A mutant having rose-shaped flowers without male and female organs in the cultivated chickpea was isolated in M2 and harvested as a single plant with its sisters sibs . In M3, inheritance of the rose-flowered mutant was studied in the segregated rows because hybridization between the mutant and parent or the other genotype of the cultivated chickpea was not possible. Results indicated that the rose-flowered mutation was controlled by a single recessive gene rs . This study is an alternative approach on inheritance studies if hybridization is impossible due to sterility